2002
DOI: 10.7164/antibiotics.55.855
|View full text |Cite
|
Sign up to set email alerts
|

GEX1 Compounds, Novel Antitumor Antibiotics Related to Herboxidiene, Produced by Streptomyces sp. I. Taxonomy, Production, Isolation, Physicochemical Properties and Biological Activities.

Abstract: Six structurally related antitumor antibiotics named GEX1 compounds were isolated from a culture broth of Streptomyces sp. GEX1A was identified as a known herbicide, herboxidiene, structurally interested by the tetrahydropyran moiety and the side chain including a conjugated diene. GEX1Q1-Q5 were determined as novel compounds related to herboxidiene. All GEX1 lines in vitro, but were not active against both Gram-positive and-negative bacteria. Though GEX1A/herboxidiene exhibited antitumor activity in murine tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 0 publications
1
64
0
2
Order By: Relevance
“…[45, 46], and both have the same mechanism of action as SSA [47, 48]. The fact that SF3B1 is the target of three different natural products extracted from diverse bacteria strains points to a shared mode of action.…”
Section: Discovery Of Small Molecule Splicing Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45, 46], and both have the same mechanism of action as SSA [47, 48]. The fact that SF3B1 is the target of three different natural products extracted from diverse bacteria strains points to a shared mode of action.…”
Section: Discovery Of Small Molecule Splicing Modulatorsmentioning
confidence: 99%
“…Madrasin was isolated from a screen of PM5 pre-mRNA splicing [56] against a library of 71,504 small molecules and also shown to inhibit splicing of endogenous genes in both HeLa and HEK293 cells [57]. Furthermore, a high-throughput screen using a luciferase splicing reporter identified clotrimazole, flunarizine, and chlorhexidine [46, 58] as splicing modulators in cultured HeLa cells. Microarray analysis of cells treated with the three compounds revealed that AS of distinct sets of genes was affected, suggesting target specificity for each.…”
Section: Discovery Of Small Molecule Splicing Modulatorsmentioning
confidence: 99%
“…Gexia (herboxidiene), first obtained from a cultured broth of Streptomyces sp., 54 has been found to be a potentially potent antitumor product associated with the induction of cell-cycle arrest in G 1 and G 2 /M phases in normal human fibroblast cell line WI-38 55 and human cervix adenocarcinoma cell line HeLa. 56 Mizukami and coworkers 56 applied the PAL assay to search for the protein targets of gexia.…”
Section: Photoaffinity Labeling Strategiesmentioning
confidence: 99%
“…Similarly, in 1997, herboxidiene was found to upregulate the expression of the LDL receptor (known to bind cholesterol from plasma for cellular uptake) and improved binding by 30 % (Brown and Goldstein 1986;Koguchi et al 1997;Sakai et al 2002a). In 2002, herboxidiene was discovered to have in vivo anti-cancer activities by inducing cell cycle arrest in the G1 and G2/M phases (Sakai et al 2002b). One of the exons was found to be skipped during the course of splicing (Sakai et al 2002a), inciting the study of herboxidiene as a pre-mRNA splicing inhibitor.…”
Section: Introductionmentioning
confidence: 98%